A new combination technique of the modified Robicsek wire fixation and plate fixation achieves effective repair of transverse sternal fracture: a report of two cases - Yoshifumi Fuke; Tomoki Ushijima; Sho Matsuyama; Satoshi Kimura; Hiromichi Sonoda; Sayaka Osawa; Jun Maki; Kentaro Tokuda; Kenta Momii; Akira Shiose (Surgical Case Reports, 2021)
Abstract Background To maximize the therapeutic effect for complicated sternal fracture, we should know advantages and disadvantages of each surgical repositioning technique, and the choice of an appropriate procedure is essential. We report two successful cases for which a combination of two existing techniques, modified Robicsek wire fixation and locked titanium plate fixation, was applied to transverse sternal fracture with flail chest. Case presentation One patient experienced a transverse sternal and rib fracture due to a traffic injury. Flail chest due to a highly displaced transverse sternal fracture made withdrawal of the ventilator impossible. Another patient, who developed fulminant myocarditis, experienced a transverse sternal fracture resulting from chest compression during cardiopulmonary resuscitation. Severe paradoxical respiratory movement was a limiting factor for cardiac and respiratory rehabilitation. In both cases, a transverse sternal fracture was difficult to correct non-invasively and indicated surgical repair. The surgical repositioning and fixation greatly contributed to the improvement of the respiratory movement, and the patients were successfully withdrawn ventilator support. Conclusion The combination of modified Robicsek wire fixation and locked titanium plate fixation for a complicated sternal fracture employs the complementary and comparative advantages of each procedure and effective fixation may be achieved.